Comparison of Social Trust's Effect on Suicide Ideation between Urban and Non-urban Areas: The Case of Japanese Adults in 2006 - Eiji Yamamura (Economics and Econometrics Research Institute (EERI), 2015)
An increasing number of studies have addressed the determinants of suicide. Social capital is a key factor in preventing suicide. However, little is known about the experience of suicide ideation using subjective values. From the viewpoint of suicide prevention, it is worth examining how people think of suicide. This paper attempts to examine the effect of social capital on suicide ideation. Furthermore, the paper compares the effect of social capital between urban and non-urban areas. In this paper, urban areas are equivalent to mega-cities with populations over one million. Non-urban areas are cities with populations of less than one million, towns and villages. Individual-level data from the Japanese General Social Surveys (JGSSs) are used. The survey, which was conducted in 2006, provides information about the subjective value of suicide ideation. The survey was answered by 1,413 subjects with a mean age of 54.5. Of the subjects, 49% were male. Social trust is used to measure the degree of social capital, and the outcome of interest is suicide ideation within the past 5 years. After controlling for various factors, the major findings are that both individual-level social trust and social trust accumulated in one's residential administrative district reduce the probability that one will consider suicide. After dividing the sample into urban and non-urban residents, particularized trust plays a role in deterring suicide ideation in urban areas, while generalized trust plays a role in deterring suicide ideation in non-urban areas. The effect of each type of trust depends on its scarcity in residential areas.
Keywords: Z13; 330; Social capital; Suicide ideation; Urban